Digging deeper into volatile organic compounds associated with cancer - Janfaza, Sajjad; Khorsand, Babak; Nikkhah, Maryam; Zahiri, Javad (Biology methods and protocols, 2019)
Volatile organic compounds (VOCs), produced and emitted through the metabolism of cancer cells or the body’s immune system, are considered novel cancer biomarkers for diagnostic purposes. Of late, a large number of work has been done to find a relationship between VOCs’ signature of body and cancer. Cancer-related VOCs can be used to detect several types of cancers at the earlier stages which in turn provide a significantly higher chance of survival. Here we aim to provide an updated picture of cancer-related VOCs based on recent findings in this field focusing on cancer odor database.